Efektivitas Layanan Fish Info Jatim dalam Sektor Perikanan - Arkani, Arlisa Rahmani Nuryadin; Pertiwi, Vidya Imanuari (VISA: Journal of Vision and Ideas, 2025)
The public service provided aims to make it easier for the community with straightforward procedures that do not disadvantage them. In today's era, the government needs to utilize technology to deliver better public services. However, Indonesia's efforts in creating effective public services have not yet been fully realized in several sectors, including the marine and fisheries sector. To help address these issues and improve services to the public, the Marine and Fisheries Office of East Java Province provides a technology-based platform such as the Fish Info Jatim website. This study aims to analyze the effectiveness of Fish Info Jatim in providing information and services to the public related to the marine and fisheries sector. This differs from previous research, which focused only on public service research in general. This study uses a qualitative research method with a case study approach. It employs the effectiveness theory of Campbell J.P with five indicators: program success, target achievement, satisfaction with the program, input and output levels, and overall goal achievement.